IMPLEMENTASI ASESMEN PORTOFOLIO DALAM MENGUKUR CAPAIAN PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN DI UPT SPF TK NEGERI SATU ATAP 01 LUBUK PAKAM - Nover Bintang Siahaan; Anita Yus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Early childhood education is a developmental process aimed at providing educational stimulation from birth through age six. Young children learn and demonstrate understanding through exploration, play, and the creation of their own works. One method that can be applied is portfolio assessment, which is used to monitor children’s developmental progress on a daily basis to encourage effective learning. The purpose of this study is to describe the types of documents collected, document artifacts, and interpret portfolio assessment data to determine the cognitive developmental achievements of young children at the UPT SPF TK Negeri Satu Atap 01 Lubuk Pakam. This study employed a descriptive qualitative research design using a narrative research method, conducted at UPT SPF TK Negeri Satu Atap 01 Lubuk Pakam, located on Jalan Patai Labu, Sekip Village, Lubuk Pakam Subdistrict, Deli Serdang Regency. Data collection was conducted through interviews and document analysis. The research results indicate that teachers at the school use portfolio assessment as an assessment of learning. The types of documents collected during the implementation of portfolio assessment at the school including evidence of products, evidence of processes, and narrative evidence can track children’s cognitive development even though they are reported at the end of the semester. Documentation of artifacts has not yet been conducted systematically. However, in determining cognitive development outcomes, teachers have used a scale of “already present” and “not yet present.” Nevertheless, the process of determining developmental achievements still has weaknesses: it is final at the end of the semester rather than a continuous process; it does not involve joint reflection between teachers and students; the evidence used is not diverse and does not sufficiently support the validity of conclusions; and specific cognitive abilities such as symbolic thinking, classification, understanding of cause and effect, and problem-solving have not been clearly identified from the portfolios.